Effects of ammonia load on amino acid utilization by growing steers - M.S. Awawdeh; K.C. McCuistion; D.P. Gnad; Evan C. Titgemeyer (Kansas Agricultural Experiment Station Research Reports, 2004)
Ruminally cannulated steers were used in two experiments to study effects of rumen ammonia load on methionine and leucine utilization. All steers were limit-fed a diet based on soybean hulls, received ruminal infusions of volatile fatty acids and abomasal infusions of glucose to provide energy, and received an abomasal infusion containing a mixture of all essential amino acids except methionine in Exp. 1 or leucine in Exp. 2. Treatments were arranged as 3 x 2 factorials and included urea (0, 40, or 80 g/day) infused ruminally and methionine (2 or 5 g/day) infused abomasally in Exp. 1 and leucine (0, 4, or 8 g/day) infused abomasally and urea (0 or 80 g/day) infused ruminally in Exp. 2. In Exp. 1, supplementation with the greater amount of methionine improved retained nitrogen, but urea infusions did not alter nitrogen retention. In Exp. 2, leucine linearly increased retained nitrogen, and urea infusions also increased nitrogen retention. The efficiency of deposition of supplemental methionine ranged between 18 and 27%, whereas that for leucine ranged from 24 to 43%. Increasing ammonia load did not negatively impact whole-body protein deposition in growing steers when either methionine or leucine was limiting.
Keywords: Cattlemen' s Day; 2004; Kansas Agricultural Experiment Station contribution; no. 04-242-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 923; Beef; Ammonia; Amino acid; Steers; Methionine; leucine